Uncertainty assessment for measurements performed in the determination of thermal conductivity by scanning thermal microscopy. (17th October 2017) - Ramiandrisoa, Liana; Allard, Alexandre; Hay, Bruno; Gomés, Séverine
Abstract: Although its use has been restricted to relative studies, scanning thermal microscopy (SThM) is presented today as a candidate technique for performing quantitative measurement of thermal properties at the nanoscale, thanks to the development of relevant calibration protocols. Based on the principle behind near-field microscopes, SThM uses a miniaturized probe to quantify heat transfers versus samples of various thermal conductivities: since the thermal conductivity of a sample cannot be directly estimated, a direct measurand related to the heat transfer must be defined and measured for each sample. That is the reason why the SThM technique applied to thermal conductivity determination belongs to the family of inverse methods. In this work we aim to qualify the technique from a metrological point of view. For the first time, assessment of uncertainty associated with the direct measurand Δ R is performed, yielding a result of less than 2%.